Kualitas Air Rawa terhadap Keluhan Kesehatan Masyarakat Desa - Norsita Agustina; Chandra Chandra; Muhammad Febriza Aquarista (Jurnal Kesehatan, 2021)
Swamp water is the source of water used Banyu Hirang Village community. The research objective is to analyze the turbidity, levels of iron and organic matter content, and community health complaints. Sampling by purposive proportional random sampling 34 people. Swamp water sampling points were carried out at 7 points, 3  from dug wells and 4 from drilled wells. Data examination of water quality in the form of turbidity, levels of iron, and organic matter content through laboratory testing in Research and Industry Standards (BARISTAND) Banjarbaru. While data with a health complaint questionnaire interviews. The study states examination physical and chemical parameters in swamp water wells exceeded the threshold-based Permenkes No.32/2017 with a maximum standard of 25 NTU, iron there are 2 points whose threshold value is less than the maximum limit of 10mg/L. In drilled wells with physical parameters of turbidity at 4 points less than the threshold, for iron at 4 points less than the threshold of 1,0mg/L and organic matter, there are 3 points where the threshold value is less than the maximum limit of 10mg/L, while 1 point of 12,86mg/L exceeds the threshold. For health complaints, there are 12% of respondents experience health complaints of red skin, 73% have complaints of itchy skin and 15% have scaly skin. Suggestions to improve health promotion, especially about the importance of treating water before use and immediately swamp allocate construction of water supply to avoid the risk of health problems.